Acquired Activated Protein C Resistance Associated with Anti-Protein S Antibody as a Strong Risk Factor for DVT in Non-SLE Patients - Nojima, Junzo; Kuratsune, Hirohiko; Suehisa, Etsuji; Kawasaki, Tomio; Machii, Takashi; Kitani, Teruo; Iwatani, Yoshinori; Kanakura, Yuzuru (Thrombosis and Haemostasis, 2002)
Anti-phospholipid (aPL) antibodies (Abs) are well known to be associated with thromboembolic events in patients with systemic lupus erythematosus (SLE). However, the clinical relevance of aPL Abs in patients without SLE (non-SLE) who have venous thromboembolism remains unclear. We evaluated 143 non-SLE patients with a first episode of clinically suspected deep vein thrombosis (DVT) by using objective tests for diagnosing DVT and laboratory tests including the activated protein C resistance (APC-R) test, the factor V Leiden test, and various aPL Abs. The prevalence of acquired APC-R, in which case there was no factor V Leiden mutation, was significantly higher in patients with DVT (15/58 cases, 25.9%, p <0.0001) than in those without DVT (3/80 cases, 3.7%), and confirmed that acquired APC-R was a strong risk factor for DVT (odds ratio [OR], 8.95; 95% confidence intervals [CI], 2.45-32.7; p <0.001). Multivariate logistic analysis revealed that the presence of LA, aCL, anti- β2-glycoprotein I, anti-prothrombin and anti-protein C Abs was not reliable as a risk factor for DVT in non-SLE patients, and that the presence of anti-protein S Abs was the most significant risk factor for DVT (OR, 5.88; 95% CI, 1.96-17.7; p <0.002). Furthermore, the presence of anti-protein S Abs was strongly associated with acquired APC-R (OR, 57.8; 95% CI, 8.53-391; p <0.0001). These results suggest that acquired APC-R may reflect functional interference by anti-protein S Abs of the protein C pathway, which action may represent an important mechanism for the development DVT in non-SLE patients.
Keywords: Acquired activated protein C resistance; anti-phospholipid antibodies; anti-protein C antibodies; anti-protein S antibodies; deep vein thrombosis